The Effects of Fiber Length and Volume on Material Properties and Crack Resistance of Basalt Fiber Reinforced Concrete (BFRC) - Xinzhong Wang; Jun He; Ayman S. Mosallam; Chuanxi Li; Haohui Xin (Advances in Materials Science and Engineering)
Basalt fiber reinforced concrete (BFRC) has been widely utilized in various constructions such as buildings, large industrial floors, and highways, due to its excellent physical and mechanical properties, as well as low production cost. In order to address the influence of basic parameters such as fiber volume fraction (0.05∼0.40%), fiber length (12∼36 mm) of BF, and compressive strength (30, 40, and 50 MPa) of concrete on both physical and mechanical properties of BFRC including compressive strength, tensile and flexural strength, workability, and anti-dry-shrinkage cracking properties, a series of standard material tests were conducted. Experimental results indicated that clumping of fibers may occur at relatively higher fiber volume fraction resulting in mixing and casting problems. Based on experimental values of mechanical properties and anti-dry-shrinkage cracking resistance of BFRC, the reasonable basalt fiber length and fiber volume fractions are identified. The addition of a small amount of short basalt fibers can result in a considerable increase in both compressive strength and modulus of rupture (MoR) of BFRC and that the proposed fiber length and content are 12.0 mm and 0.10%∼0.15%, respectively. As the length of basalt fibers increases, the development of early shrinkage cracks decreases initially and then increases slowly and the optimal fiber length is 18.0 mm. Results of the study also indicated that early shrinkage cracks decrease with the increase of fiber volume fraction, and when the volume fraction of 0.20% is used, no cracks were observed. All the findings of the present study may provide reference for the material proportion design of BFRC.